Development of Smart Building Training Kit for Control System Competencies in Vocational High Schools - Pujirianto, Pujirianto; Haryanto, Haryanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
The unavailability, lack of updates and inappropriateness of learning media results in low-quality learning outcomes. The right learning media is an important part of the learning process, especially practicum learning in Vocational High School (VHS). The objectives of the research are to obtain: (1) Products in the form of smart building training kits as learning media equipped with Supervisory Control and Data Acquisition (SCADA) system based on Industrial Internet of Things (IIoT) for VHS in learning control systems; (2) The feasibility level of the training kit; (3) The effectiveness of the use of training kits. Development research refers to the ADDIE model developed by Branch. The study results are as follows: (1) The product in the form of a training kit consists of a component training kit and a simulator equipped with a job sheet and a manual. (2) The training kit is considered very feasible. The expert assessment of the feasibility of the product is 95.5% (very feasible category). The teacher's user response gave a rating of 95.5% (very feasible category). The user response by graduates gave an assessment of 90.8% (very feasible category). (3) The use of training kits has significant effectiveness on students' learning outcomes based on the results of the Paired Sample T-test and Independent Sample T-test with a sig value (2-tailed) (0.000) < 0.05. It can be concluded that a smart building training kit is an appropriate, very feasible, and effective learning medium for use in learning control systems.